Hoop crazy : the lives of Clair Bee and Chip Hilton - Gildea, Dennis (University of Arkansas Press, 2013)
Clair Bee (1896-1983) was a hugely successful basketball coach at Rider College and Long Island University with a 412 and 87 record before his career was derailed in 1951 by a point-shaving scandal. In the trial that sent his star player, Sherman White, to prison, the judge excoriated Bee for creating a morally lax culture that contributed to his players' involvement with gambling. To a certain extent, Bee agreed with the judge's scolding, concluding that coaches, himself included, had become so driven to succeed on the court that they had lost sight of the educational role sports should play. His coaching career effectively over, Bee launched an effort to reform the ills he saw in college sports, and he did so in the pages of the Chip Hilton novels for young readers. He began the series in 1948, but it was the post-scandal books that he used as teaching tools. The books mirrored some of the events of the gambling scandal and were Bee's attempt to reform the problems plaguing college sports. He used his fiction to posit a better sports world that he hoped his young readers would construct and inhabit. The Chip Hilton books were extremely popular and have become a classic series, with over two million copies sold to date. Hoop Crazy is the fascinating story of Clair Bee and his star character Chip Hilton and the ways in which their lives, real and fictional, were intertwined.